What is the Evidence for the Pharmacological Management of Nausea and Vomiting in Inoperable Malignant Bowel Obstruction? - Barnes, Ellen; Blount, Eoghan; Buckley, Katie; Carter, Ellen; Dwyer, Liam; Loughman, Emily; Myles, Helena (Trinity Student Medical Journal, 2020)
The objective is to systematically review the evidence available for the pharmacological management of nausea and vomiting in inoperable malignant bowel obstruction. PubMed, EMBASE and clinicaltrials.gov were searched using the following terms: Nausea, Vomiting, Cancer, Inoperable Bowel Obstruction, Malignant Bowel Obstruction. The search identified 699 studies and 1 from an additional source. With the inclusion and exclusion criteria applied 12 papers were selected. Of the 12 studies, 6 RCTs were identified that compared the somatostatin analogue octreotide or lanreotide. Two of these RCTs also compared octreotide to hyoscine butylbromide, and four with placebo. Octreotide was shown to significantly reduce nausea and vomiting. One study however, found that octreotide did not significantly reduce vomiting compared to a placebo. Prospective studies, retrospective studies and non-randomised clinical trials were also identified. They assessed the use of octreotide, granisetron or olanzapine. They found that there was significant improvement in nausea or vomiting episodes. Despite not being the first line treatment Octreotide appears to be the most studied and researched drug. In all but one study it has been found to have a positive outcome. This review has highlighted the lack of information or research available on other antiemetic or anti-nausea medications, despite their widespread use.